WACSI : striving for sustainability - Moyo, Bhekinkosi; Bowen, Amanda (London : Wits Business School, 2019)
By late March 2018, with the economy improving in West Africa in general, and in Ghana in particular, civil society organisations (CSOs) in the region were feeling the pinch of decreased funding from international donors, who now preferred to provide funding where they perceived the need to be greater. Nevertheless, Nana Asantewa Afadzinu, executive director of the West Africa Civil Society Institute (WACSI), an organisation dedicated to empowering and strengthening the capacity of CSOs in the region, believed that their work remained as important as before. Since 2013, as a means of ensuring that its work could continue, WACSI had taken steps to diversify its donor base, generate its own income and strengthen internal sustainability. Ahead of a board meeting to discuss the organisation's 2018-2022 strategy, Afadzinu wondered whether WACSI's strategies to ensure its future sustainability would succeed.
Originally Published In Moyo, B., & Bowen, A. (2019). WACSI: Striving for Sustainability. WBS-2019-11. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; West Africa Civil Society Institute; Nonprofit organizations -- Africa, West -- Finance; Civil society -- Africa, West